Web-based educational tools and decision aids for patients with advanced cancer: a systematic review - Ullrich, Phoebe; Voß, Henrike; Unsöld, Laura; Thomas, Michael; Villalobos Bollen, Matthias Americo (Patient education and counseling, 2025)
Objectives - To provide an overview of existing interactive web-based educational tools and decision aids for patients with advanced cancer and to evaluate their development process, content, feasibility, usability, and effectiveness. - Methods - Systematic literature search from inception to November 2023; screening with Covidence software; narrative analysis of results and quality assessment with the SUNDAE checklist. - Results - Sixteen web-based tools were identified: Seven for breast cancer, six for other specific cancers, and three for mixed populations. Studies predominantly used literature reviews, focus groups, and/or pre-existing tools for the development. The tools were heterogeneous and not all integrated aspects of end-of-life care. User tests included controlled trials, prospective interventional cohort studies, and a retrospective observational study, involving a total of 6192 patients. Results showed partially low adoption and infrequent use. Feasibility and usability were positively rated with high rates of user satisfaction. Preparation for and involvement in decision-making was partially supported by increased knowledge and improved doctor-patient relationships. Effects on involvement and self-efficacy in decision-making, participation, and distress were uncertain. Effects on quality of life, hope, anxiety, engagement in palliative care/advance directives, and survival were not found. - Conclusions - Despite high user satisfaction and adequate feasibility and usability, the evidence for other outcomes is diverse and low for long-term implementation. Tools are very heterogeneous in cancer entities and content. Although targeting patients with advanced cancer not all tools integrate aspects of palliative care and end-of-life. - Practice implications - In advanced cancer care, patient involvement in decision-making is complex. Web-based solutions are promising because of easy accessibility and dissemination and the ability to adapt information to patients’ needs and new treatment developments. Still, only a few evidence-based web-based educational tools and decision aids are available. Filling this gap is essential to empower patients to make informed and goal-concordant treatment decisions.